Incorporación de los delitos informáticos al Código Penal del Estado de Michoacán - Mora de la Peña, Eréndira (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
This thesis is a dogmatic criminal legal analysis, by means of which we can then understand novel legally criminal figures, for which it was consulted to prestigious writers, which will shape their theories according to the computer crime, both in the Federal legislation such as the various States, with emphasis on the state. In the same way we will link the Computing with various human activities such as medicine, biology, genetics and many others, as well as the importance to the right, and his innovative branches as they are: the cyber law, the legal informatics, the right to the cybernetic information and legal links with other branches such as with the constitutional law, civil law, the copyright, the right to information, the banking law, and especially the criminal law, which is the level of analysis of this thesis, and it is in where is located the cybercrime. We develop a detailed description of the nature Of the computer crime and the framework that is interlinked with our criminal figures, where will be the legal property is state guardianship and protects, and by means of which laws it succeeds as it is the Constitution of the United Mexican States, secondary laws or regulations as are: the federal law of copyright, the industrial property law, the law of transparency and public access to government information, as well as the civil and penal codes federal and state civil procedural codes and federal and state criminal and the laws of the States that already analyzed the computer crime that we can serve as an analysis for the proposal of the incorporation of computer crime to our regulation of criminal law of the State. We check the offender that performs the unlawful behavior, and we will discover the importance that must have the prevention of computer crime in our country as well as the significance of their supervision the cyber police.

Esta tesis, es un análisis dogmático Jurídico Penal, examinaremos jurídicamente novedosas figuras penales; para esto se consulto prestigiados tratadistas, de los cuales plasmaremos sus teorías en los delitos informáticos, tanto en las legislaciones Federales como en la de los diversos Estados. Vincularemos la Informática con diversas actividades humanas tal como la medicina, la biología, la genética, entre muchas otras, así como la importancia con el Derecho y sus novedosas ramas como lo son: el Derecho informático, la informática jurídica, el Derecho a la información cibernética jurídica y su vinculación con otras ramas como con el Derecho constitucional, el Derecho civil, el Derecho procesal civil, el Derecho de autor, el Derecho a la información, el Derecho bancario y, sobretodo, el Derecho penal, que es el plano de análisis de ésta tesis de grado, y es en donde se encuentran los delitos informáticos. Desarrollamos una descripción de la naturaleza de los delitos informáticos y del marco en que se encuentra interrelacionado con nuestras figuras delictivas, en donde se establecerán los bienes jurídicos que el estado tutela y por medio de que legislaciones lo logra: como la Constitución Política de los Estados Unidos Mexicanos, las leyes secundarias a saber: la ley federal del Derecho de autor, la ley de propiedad industrial, la ley de transparencia y acceso a la información pública gubernamental, los códigos civiles; penales federales y estatales, los códigos procesales civiles y penales federales y estatales. Las legislaciones de los estados que analizan ya los delitos informáticos y que servirán de análisis para la propuesta de la incorporación de los delitos informáticos a nuestra regulación penal del Estado.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2014-0875; Delito informático; Delincuencia organizada; Policía informática; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/573